(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Density, age and spatial structures of cenopopulations of Stipa dasyphylla, one of the main tussock cenosoformative species of steppe phytocenoses, are researched in the south-east of Ukrainian. Actual state of S. dasyphylla populations may be used to apprise whole plant communities in natural reserves.